Practices of Teaching and Learning in ABESIT:A Case Presentation of Even Semester 2015-16 and Odd Semester 2016-17 - Mehra, Pawan Singh; Agarwal, Gaurav (Journal of Engineering Education Transformations, 2025)
The educational governing bodies such as UGC, AICTE which are responsible for the quality of Higher Education in India emphasize on adopting the best practices in Teaching-Learning to yield superior results. In past few decades, several Engineering Colleges and Universities have been established, especially after the establishment of All India Council for Technical Education (AICTE). The conventional curriculum and traditional teaching-learning in academics have proved to be less effective in terms of design and delivery of pedagogy, which needs regular revision to ensure quality education in India. In this paper, qualitative and quantitative analysis of Teaching-Learning practices in ABES Institute of Technology (ABESIT) has been carried out.